Prevalence and management of diabetes and metabolic risk factors in Thai adults: The Thai national health examination survey IV, 2009 - Wichai Aekplakorn (2018)
OBJECTIVE - To determine the prevalence of impaired fasting glucose (IFG) and undiagnosed and diagnosed diabetes in Thai adults in 2009 and examine the extent of changes in proportions of diagnosis, treatment, and control for blood glucose, high blood pressure, and high total cholesterol between 2004 and 2009. RESEARCH DESIGN AND METHODS - Data from the multistage cross-sectional National Health Examination Survey (NHES) IV of 18,629 Thai adults aged ≥20 years conducted in 2009 were used to analyze and compare with the data from NHES III in 2004. RESULTS - The prevalence of IFG and diabetes was 10.6 and 7.5%, respectively. Of all diabetes diagnoses, 35.4% were not previously diagnosed, and the proportion was higher in men than in women (47.3 vs. 23.4%, P < 0.05). Compared with those in year 2004, the proportions of individuals with diabetes and concomitant hypertension did not significantly decrease in 2009 in both sexes, but the proportions of women with diabetes who were abdominally obese or had high total cholesterol (≥5.2 mmol/L) significantly increased in 2009 by 18.0 and 23.5%, respectively (all P < 0.01). The rates of treatment and control of blood glucose, high blood pressure, and high total cholesterol were favorably improved in 2009. However, in substantial proportions of individuals with diabetes these concomitants were still controlled suboptimally. CONCLUSIONS - The prevalence of diabetes and IFG remained high in Thai adults. Improvement in detection and control of diabetes and associatedmetabolic risk factors, particularly obesity and high serum cholesterol, are necessary. © 2011 by the American Diabetes Association.